Pathogenesis of Frontotemporal Lobar Degeneration: Insights From Loss of Function Theory and Early Involvement of the Caudate Nucleus - Sobue, Gen; Ishigaki, Shinsuke; Watanabe, Hirohisa (Frontiers in Neuroscience, 2018)
Frontotemporal lobar degeneration (FTLD) is a group of clinically, pathologically and genetically heterogeneous neurodegenerative disorders that involve the frontal and temporal lobes. Behavioral variant frontotemporal dementia (bvFTD), semantic dementia (SD) and progressive non-fluent aphasia (PNFA) are three major clinical syndromes. TDP-43, FUS, and tau are three major pathogenetic proteins. In this review, we first discuss the loss-of-function mechanism of FTLD. We focus on FUS-associated pathogenesis in which FUS is linked to tau by regulating its alternative splicing machinery. Moreover, FUS is associated with abnormalities in post-synaptic formation, which can be an early disease marker of FTLD. Second, we discuss clinical and pathological aspects of FTLD. Recently, FTLD and amyotrophic lateral sclerosis (ALS) have been recognized as the same disease entity; indeed, nearly all sporadic ALS cases show TDP-43 pathology irrespective of FTD phenotype. Thus, investigating early structural and network changes in the FTLD/ALS continuum can be useful for developing early diagnostic markers of FTLD. MRI studies have revealed the involvement of the caudate nucleus and its anatomical networks in association with the early phase of behavioral/cognitive decline in FTLD/ALS. In particular, even ALS patients with normal cognition have shown a significant decrease in structural connectivity between the caudate head networks. In pathological studies, FTLD/ALS has shown striatal involvement of both efferent system components and glutamatergic inputs from the cerebral cortices even in ALS patients. Thus, the caudate nucleus may be primarily associated with behavioral abnormality and cognitive involvement in FTLD/ALS. Although several clinical trials have been conducted, there is still no therapy that can change the disease course in patients with FTLD. Therefore, there is an urgent need to establish a strategy for predominant sporadic FTLD cases.